Validation of EN 12354-1 prediction models by means of Intensity and Vibration measurement techniques in Spanish buildings involving flanking airborne sound transmission - Andrade, C.A.R. (2010)
Flanking transmission in building structures can be estimated using the Intensity technique according to the method described in the standard EN 15186-2 Annex C. This can also be done by using Vibration measurement technique. In situ conditions, the junctions of a room show different behaviours when compared to those obtained in laboratory. Measurements were performed to compare the results obtained by the pressure measurement procedure according to EN 140-4 and the prediction results obtained by the methods described in the standard EN 12354-1. Also the Intensity measurement technique was used to evaluate the contribution of each wall and flanking paths, which were compared with the results obtained by the Vibration measurements procedure. The main issue is to use the prediction models previously referred for validation to the particular Spanish buildings.